MODEL OF EVALUATION INFORMING OF DIFFERENTIAL PRESENTATION - Бараннік, В. В.; Шинкарев, В. В.; Ширяев, А. В. (Science-based technologies, 2009)
Actuality improves the timeliness and reliability of information delivered on the basis of methods of compact representation.One of the most effective approaches for reducing redundancy in realistic images without losingtheir quality, based on the construction of a differential description.